Investigation of the Sound Absorption and Transmission Loss Performances of Green Homogenous and Hybrid Luffa and Jute Fiber Samples - (:unkn) unknown (My University, 2021)
In order to promote the use of natural fibers in noise and vibration applications, the properties of these structures should be fully identified. The sound absorption coefficients (SACs) and transmission losses (TLs) of green luffa fiber samples are thoroughly investigated and their acoustic performances are compared with the acoustic performances of green homogenous jute and hybrid jute/luffa fiber samples in this study. For this purpose, green homogenous luffa and jute fiber samples and their green hybrid fiber samples with different thicknesses (10, 20, 30, and 40 mm) are produced and their SACs and TLs are determined using the impedance tube method. First, the methods for the experimental identification of acoustic properties are presented and the variations in the measured acoustic properties are identified. After that, the effects of sample thickness on the acoustic performances of homogenous luffa as well as jute samples and their hybrid fiber samples as a function of frequency are explored. The thickness-dependent tendencies of the SACs and TLs of homogenous and hybrid luffa and jute fiber samples for low, medium and high frequency ranges are determined. Then, the acoustic performances of the homogenous and hybrid luffa and jute samples are compared and evaluated. The results and analyses for the acoustic properties of homogeneous luffa and jute fiber samples and their hybrid fiber samples for a variety of thicknesses and different frequencies presented here can be used to design homogenous as well as hybrid luffa and jute fiber structures in practical applications.